(untitled) (International Journal of Engineering and Computer Science, 2015)
As an emerging technology and business paradigm, Cloud computing platforms provide easy access to a company’s high-performance, computing and storage infrastructure through web services. Cloud computing gives numerous profits to the clients, for example approachability and accessibility. As the information is accessible over the cloud, it might be gained entrance to by diverse clients. There may be delicate information of association. This is the one issue to give access to validated clients only. But the data can be accessed by the owner of the cloud. So to abstain from getting information being gained entrance to by the cloud manager, we will utilize the different encryption algorithms to encrypt the data available over the cloud which in turn will give security to the information and only authenticated users will get access to the secure data over the cloud. Duplication of Data is a technique for reducing the amount of storage space, an organization needs to save its data. The proposed system supports authorized duplicate check in hybrid cloud architecture. Proposed authorized duplicate check scheme acquires minimal overhead compared to normal operations. To reduce the weaknesses of convergent encryption, we are proposing LFSR (Linear Feedback Shift Register) encryption technique. Security analysis determines that this system is secure in terms of the definitions specified in the proposed security model.